2014
DOI: 10.1590/1982-370002332013
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de Vida e Sobrecarga de Cuidadores de Crianças com Câncer

Abstract: O objetivo do estudo foi verificar a relação entre a qualidade de vida e a sobrecarga em cuidadores de crianças portadoras de neoplasia e assistidas em uma casa de apoio. A metodologia foi quantiqualitativa com a utilização de multimétodos de pesquisa. Os participantes (N = 23) foram os cuidadores dos pacientes acompanhados pela Casa de Apoio à Criança com Câncer. Os instrumentos de coleta de dados foram: um questionário sociodemográfico, a Escala Whoqol - Bref, a Escala Zarit e uma entrevista por pautas. A an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
23

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 16 publications
0
9
1
23
Order By: Relevance
“…The strain on family relationships was very evident caused by the very treatment and hospitalization which these mothers go through, and a certain confinement resulting from this situation showing social overload. This result differs from another study that assessed the consequences of child cancer in family life and which indicated that the social problem for the families was resolved by being together with their child during hospitalization (12) . Nevertheless, it is worth emphasizing that it is normal for the parents of severely ill children to focus on their children's quality of life, defend them and put their child`s needs above their own (26) .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The strain on family relationships was very evident caused by the very treatment and hospitalization which these mothers go through, and a certain confinement resulting from this situation showing social overload. This result differs from another study that assessed the consequences of child cancer in family life and which indicated that the social problem for the families was resolved by being together with their child during hospitalization (12) . Nevertheless, it is worth emphasizing that it is normal for the parents of severely ill children to focus on their children's quality of life, defend them and put their child`s needs above their own (26) .…”
Section: Discussioncontrasting
confidence: 99%
“…Another study that assessed quality of life and overload of caregivers of children with neoplasms also identified the psychological domain as the most affected one, and in addition to this there was also a prevalence of women as participants in the study, meaning those responsible for caring for other family members (12) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 These individuals' life becomes intensely overloaded, with changes in the family routine, relinquishments of personal, social and professional activities, and financial implications. 2,4,5 In addition, the overload caused by this pursuit can have a psychoemotional repercussion on these family members and affect their relationship with their children and/ or adolescents. 6 Uncertainty and insecurity are present in these individuals' life, and the final goal of the experience is not necessarily the cure of cancer, but the way in which each stage of the process was experienced.…”
Section: Introductionmentioning
confidence: 99%